Соціально-комунікаційний аспект формування інтересу до книги за допомогою Інтернету - Бессараб, Анастасія (Видавництво Львівської політехніки, 2016)
It is shown main social and communication ways of development motivation to reading Ukrainian book in Internet: site, page in social media, blog, channel in YouTube, booktrailer, online-TV etc.
Keywords: Internet; book; publisher; author; reader; site; social media